PENGARUH CAFÉ ATMOSPHERE, FOOD QUALITY DAN SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION DAN REPURCHASE INTENTION - Wiwoho, Gunarso (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2014)
This study aims to examine and analyze the effect of café atmosphere, food quality, service quality on customer satisfaction and repurchase intention on consumers in the Beranda Eatery Kebumen. The purpose of this study is to analyze and explain the influence between independent variables, intervening variables and dependent variables.The population of this research is the consumer of the Beranda Eatery Kebumen. The sample in this study is 100 people. The sampling technique used was accidental sampling. The method of data collection with questionnaire. Respondents' attitudes are measured with a 4-level Likert scale and the data obtained are processed by SPSS (Statistical Product and Service Solution) analysis for Windows version 22. Data analysis uses descriptive analysis, and statistical analysis (path analysis).The results showed that there was a significant influence between café atmosphere variables on customer satisfaction, food quality had a significant effect on customer satisfaction, then service quality had a significant effect on customer satisfaction, cafe atmosphere had a significant effect on repurchase intention, food quality had no significant effect on repurchase intention, service quality has a significant effect on repurchase intention, and customer satisfaction has a significant effect on repurchase intention.